2007
DOI: 10.1002/pd.1707
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of a ring chromosome 15 in a fetus with intra uterine growth retardation and diaphragmatic hernia

Abstract: This case support the evidence that the region 15q26.3 is implicated in intrauterine growth retardation and suggests that the 15q critical region implicated in congenital diaphragmatic hernia is localized in 15q26.1-q26.2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…In the ring chromosome 15 in this present study, the fetus had CDH and intrauterine growth retardation. Britto et al [2014] and Hatem et al [2007] each reported a case of prenatal diagnosis of CDH and intrauterine growth retardation in a fetus with ring chromosome 15 similar to our study. Klaassens et al [2007] reported 2 patients with a deletion of 15q26 and the phenotype consists of intrauterine growth retardation, left-sided CDH, cardiac anomalies, and characteristic facial features, similar to those seen in Fryns syndrome.…”
Section: Discussionsupporting
confidence: 78%
“…In the ring chromosome 15 in this present study, the fetus had CDH and intrauterine growth retardation. Britto et al [2014] and Hatem et al [2007] each reported a case of prenatal diagnosis of CDH and intrauterine growth retardation in a fetus with ring chromosome 15 similar to our study. Klaassens et al [2007] reported 2 patients with a deletion of 15q26 and the phenotype consists of intrauterine growth retardation, left-sided CDH, cardiac anomalies, and characteristic facial features, similar to those seen in Fryns syndrome.…”
Section: Discussionsupporting
confidence: 78%
“…Hatem et al [12] described a woman 27 years-old, gravida 1, para 0, with a fetus at 18-week gestation with IUGR, oligohydramnios, CDH with liver herniation, and polycystic kidneys. Karyotype was 46,XX,r(15) and FISH revealed loss of 15q26.1-qter region.…”
Section: Discussionmentioning
confidence: 99%
“…Although ring chromosome 15 is related to variable phenotypes, most recurrent findings are severe growth deficiency, mental retardation, and dysmorphic features [12]. Severe growth deficiency is a common findings in the ring chromosome 15 because of loss of the insulin-like growth factor I receptor gene located in 15q26.3 [1, 9, 10, 12]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ring chromosome 15 r(15) is a rare anomaly both in “pure” and in mosaic forms [1]; so far, only ~50 cases were described [2], and only three cases so far have been reported in prenatal diagnosis [24] and just one with a twenty-year cytogenetic and molecular followup [5]. Previous studies showed that ring chromosome 15 results in a varied and unspecific phenotype [6, 7].…”
Section: Introductionmentioning
confidence: 99%